THE PERCEPTION OF THE REPRESENTATIVES OF NGOS REGARDING THE COLLABORATION BETWEEN PUBLIC SECTOR AND NON-PROFIT ORGANIZATIONS TOWARD SOCIAL SERVICES FOR FAMILIES (NORTH ALBANIA CASE) - Lumanaj, Brilanda (European Scientific Journal, ESJ, 2014)
Family is evaluated as a principal source of human capital. The process of decentralization increases the responsibility of local governance structures to support families with social services. One of the key elements while offering social services is the collaboration between local governance and civil society organizations. The paper aims to explore and evaluate the collaboration of the public sector of social services with the representatives of non-profit organizations. This collaboration is analyzed through the perceptions of representatives of NGOs. Furthermore, it is an objective of this study to explore the strengths and weaknesses points of this collaboration and what they suggest to improve it. The study was done in the northern region of Albania, including her four Districts, in its main cities: Shkodër, Lezhë, Kukës and Peshkopi. A qualitative research method has been used. The instrument used for data gathering is the semi-structured interviews. In this study participated 21 representatives of non-profit organizations that operate in the field study. The findings show that the representatives of NGOs, in most cases, suggest the improvement of collaboration with the local governance. It is necessary to improve and implement the legal framework and it is necessary to increase the financial support of NGOs regarding the social services for families.